Coumarin derivatives as fibronectin-binding protein A inhibitors against bone and joint infections by Staphylococcus aureus: Molecular docking and pharmacological profiling - Thu Minh Nguyen, Luan Luong Chu* (Vietnam Journal of Science, Technology and Engineering, 2026)
Bone and joint infections remain a serious clinical problem, with Staphylococcus aureus being one of the causative agents. A key factor in the early stage of infection is fibronectin-binding protein A (FnBP-A), which mediates bacterial adhesion to host fibronectin in the extracellular matrix. The increasing prevalence of antibioticresistant S. aureus, particularly methicillin-resistant strains (MRSA), highlights the need for alternative therapeutic strategies targeting bacterial adhesion. Coumarins have attracted attention as potential antimicrobial agents because of their broad biological activities and reported anti-S. aureus effects. In this study, selected coumarin derivatives were evaluated for their inhibitory potential against the FnBPA-fibronectin complex using molecular docking with AutoDock Vina and AutoDock4. Compounds with favourable binding profiles were further assessed for predicted pharmacological properties. Among the tested compounds, frutinone A and phyllocoumarin showed stronger docking affinities than vancomycin HCl, a commonly used antibiotic for S. aureus-associated bone and joint infections. In addition, pharmacological predictions supported their potential for further investigation. These findings suggest that coumarin derivatives, particularly frutinone A and phyllocoumarin, may serve as promising candidates for the development of anti-adhesive agents against S. aureus-related bone and joint infections.